Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw II Terhadap Hasil Belajar Pada Mata Kuliah Fisologi Hewan - Mohammad Mulyadi Prasetyo; Nurhidayah; Muqtakdir Nurfalaq Syarif (Al-AHYA: Jurnal Pendidikan Biologi, 2023)
This study aims to ascertain the impact of the Jigsaw II cooperative model on learning outcomes in the course of animal physiology. The study used a one-group pretest-posttest design with a random sampling approach. Further, this study focused on the students who attended an animal physiology course during the even semester. Learning achievement tests were used to collect data on learning outcomes. Data were collected using learning achievement tests to measure student learning outcomes, and then they were analyzed descriptively, namely by mean, median, mode, variance, and standard deviation. The study's hypothesis was then verified using inferential analysis using a paired sample t-test. The results showed that the Jigsaw II cooperative learning model had a strong influence on student learning outcomes in the animal physiology course. The acquisition of a higher post-test average score, which stands at 74.96 as opposed to the pretest score of just 60.17, is indicative of these results. This study's conclusion shows that learning through the Jigsaw II cooperative model can improve the quality of learning in the cognitive domain.